(untitled) (World Science, 2019)
One of the most common childhood diseases is infectious mononucleosis (IM), which Epstein-Barr virus (EBV) is a causative factor. According to WHO statistics, more than 5 million children die every year from the indicated infectious pathology and its consequences in the world. Streptococcus pyogenes, Streptococcus pneumoniae and other Streptococcus, Enterococcus, Lactobacillus Actinomices, Neisseria, Actinomyces, Clostridium, Pseudomonas, Staphylococus epidermidis, Staphylococus aureus are most often detected in the oral cavity and nasopharynx. In the available literature there are practically no works that would consider the effect of microbial flora of the mucous membrane of the rhinopharynx on the formation of the immune response of children with IM.